Is there an increased cardiovascular risk in patients with prolactinoma? A challenging question - YAVUZ, DİLEK; SÜNBÜL, MURAT (WILEY, 2021)
Purpose Epicardial adipose tissue thickness (EATT) is considered to be a surrogate for visceral fat and a novel cardiovascular risk indicator. Hyperprolactinemia has been shown to be associated with increased cardiovascular risk. The aim was to evaluate the association between EATT, carotid intima media thickness (CIMT), and cardiac functions in patients with prolactinoma. Methods Patients with the diagnosis of prolactinoma were included. The control group consisted of healthy age matched individuals with normal prolactin levels. Prolactin, fasting blood glucose (FBG), insulin, hemoglobin A1c (HbA1c), alanine aminotransferase (ALT), total cholesterol, triglycerides, and high (HDL) and low density lipoprotein (LDL) cholesterol were measured. EATT, CIMT, cardiac systolic, and diastolic functions were determined using echocardiography. Results We evaluated 67 patients with prolactinoma (aged 40.7 +/- 11.9 years, F/M: 51/16) and 57 controls (aged 42.5 +/- 7.4 years, F/M: 36/21). Of the 67 patients, 24 had normal prolactin levels. FBG level was higher in prolactinoma patients than in controls. Patients and controls had similar HbA1c, HOMA-IR, ALT, total, HDL, LDL cholesterol, and triglycerides levels, and similar cardiac systolic and diastolic functions. Prolactinoma patients had greater EATT (3.0 +/- 0.5 mm vs. 2.6 +/- 0.4 mm, p < 0.001) and CIMT (0.57 +/- 0.08 mm vs. 0.52 +/- 0.04 mm, p = 0.03) than controls. EATT was correlated with body mass index, FBG, HbA1c, and triglyceride levels. Conclusions EATT and CIMT were greater in patients with prolactinoma, although they had normal cardiac systolic and diastolic functions.
Keywords: cardiovascular risk; carotid intima media thickness; echocardiography; epicardial adipose tissue thickness; prolactinoma; EPICARDIAL ADIPOSE-TISSUE; PRECLINICAL ATHEROSCLEROSIS; ANDROGEN DEFICIENCY; INSULIN-RESISTANCE; LOW TESTOSTERONE; FAT; HYPERPROLACTINEMIA; ECHOCARDIOGRAPHY; POPULATION; THICKNESS